Diagnosing heart failure with preserved ejection fraction. (September 2013) - Becher, Peter Moritz; Lindner, Diana; Fluschnik, Nina; Blankenberg, Stefan; Westermann, Dirk
Abstract : Introduction: Heart failure with preserved ejection fraction (HFPEF) is a common syndrome, accounting for about 50% of all patients with heart failure (HF). Morbidity and mortality are similar to patients with HF with reduced ejection fraction (HFREF), yet no effective treatment has been identified in randomized clinical trials. Areas covered: This article provides an overview of the available literature regarding diagnosing established HFPEF and potential new therapeutic targets for the early diagnosis of HFPEF. Vascular dysfunction, ventricular–arterial coupling, oxidative stress, extracellular matrix regulation, chronotropic incompetence, pulmonary hypertension, exercise testing and biomarkers were taken into consideration next to conventional measurements of diastolic dysfunction. Expert opinion: Measuring diastolic dysfunction in HFPEF is considered important in many patients. Nevertheless, today we know that other causes besides diastolic dysfunction are also involved in the pathophysiology of many HFPEF patients and need to be investigated in order to make a correct diagnosis. Therefore, further research is required to allow better and more specific diagnostic and treatment options to reduce the morbidity and mortality for this ever-expanding HF population.